Glass Green Sheet
Patent Information
- Application Number
- JP2025059448
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0014】 前記第1発明のガラスグリーンシートによれば、アクリル系バインダー、可塑剤、離型剤、および、消泡剤を含む有機成分は、前記ガラスグリーンシート全体に対して9wt%以上14wt%以下で含まれるので、積層されて保管される場合において、グリーンシート同士の張りつきを低減できる。
Smart Images

Figure 2026166485000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a glass green sheet, and particularly relates to a technique for improving the storage stability of a glass green sheet. BACKGROUND ART
[0002] In a Solid Oxide Fuel Cell (SOFC), a fuel electrode (anode) and an air electrode (cathode) are arranged to face each other with a solid electrolyte, which is a dense layer containing an oxide ion conductor, interposed therebetween. A gas pipe for supplying gas is connected to an electrode (for example, the fuel electrode) of such an SOFC, and a desired gas is supplied to the electrode through the gas pipe. In an SOFC having such a structure, supply of an inappropriate gas to the electrode may cause deterioration of power generation performance and safety, so a gas sealing portion is formed at a connection portion with the gas pipe and the like. Such a gas sealing portion is formed by attaching a sealing green sheet containing glass as a main component to an object to be sealed, and then performing firing at a temperature equal to or higher than the glass softening point to effect fusion and solidification.
[0003] The sealing green sheet for forming the glass sealing portion contains, in addition to glass as a main component, various organic substances such as a binder and a plasticizer, and a solvent. Among the organic substances described above, the binder has a function of binding respective components in the green sheet to enhance the shape integrity of the sheet. The plasticizer also has a function of imparting strength, flexibility and moisture retention to the green sheet.
[0004] An example of such a sealing green sheet containing glass and an organic substance is disclosed in Patent Document 1. Patent Document 1 discloses a sealing green sheet that requires, for example, that the addition amount of a plasticizer is 1 wt% or more and 4.8 wt% or less when the glass material is taken as 100 wt%. PRIOR ART DOCUMENTS PATENT DOCUMENTS
[0005] PATENT DOCUMENT 1 Japanese Patent Publication No. 2020-167093 [Overview of the project] [Problems that the invention aims to solve]
[0006] Incidentally, typical sealing green sheets are stored stacked in layers after manufacturing. In this process, depending on the number of sheets stacked and the storage period, the sheets may stick together. When such sticking occurs, the sheets need to be separated when used, but this can cause the sheets to tear, resulting in defective products and, consequently, a decrease in product yield. This problem arises, for example, because the binder material that makes up the green sheet itself has an adhesive effect.
[0007] To address this problem, one could consider placing a paper-like material between the sheets during storage to reduce sticking. However, this would increase the labor required for the insertion process, and the inserted paper would become waste when the sheets are used.
[0008] This invention was made against the above circumstances, and its objective is to provide a glass green sheet that reduces sticking between sheets even when stored in a stacked state.
[0009] Based on the above circumstances, the inventors of this invention conducted various studies and found that by limiting the organic components in the granulated powder used to create the green sheet to a specific range, it is possible to produce a green sheet with less sticking. This invention is based on this finding. [Means for solving the problem]
[0010] In other words, the gist of the first invention is a glass green sheet characterized by (a) containing glass powder, an aqueous solvent, and an organic component, (b) the organic component comprising an acrylic binder, a plasticizer, a mold release agent, and an antifoaming agent, and (c) the organic component being 9 wt% or more and 14 wt% or less of the total glass green sheet.
[0011] The gist of the second invention is that, in the glass green sheet of the first invention, the glass powder has a D50 particle size of 10 μm or more and 30 μm or less.
[0012] The gist of the third invention is that the glass green sheet of the first or second invention is used to form the gas sealing portion of a solid oxide fuel cell.
[0013] The gist of the fourth invention is that, in the glass green sheet of any one of the first to third inventions, the glass powder is borosilicate glass. [Effects of the Invention]
[0014] According to the glass green sheet of the first invention, the organic components, including an acrylic binder, plasticizer, release agent, and defoamer, are contained in an amount of 9 wt% to 14 wt% of the total glass green sheet, thereby reducing the adhesion between the green sheets when they are stored in a laminated state.
[0015] According to the glass green sheet of the second invention, since the D50 particle size value of the glass powder is 10 μm or more and 30 μm or less, when the green sheets are stored in a stacked manner, sticking between them can be reduced.
[0016] According to the glass green sheet of the third invention, which is used for forming the gas sealing portion of a solid oxide fuel cell, the sticking between green sheets is reduced when they are stacked and stored, so that each sheet can be suitably supplied when forming the gas sealing portion.
[0017] According to the glass green sheet of the fourth invention, since the glass powder is borosilicate glass, a glass having excellent heat resistance and hardness can be obtained when fired. [Brief Description of the Drawings]
[0018] [Figure 1] It is a diagram illustrating a manufacturing process according to one embodiment of the glass green sheet of the present invention. [Figure 2] It is a cross-sectional view schematically showing an aspect of a sticking evaluation test according to one embodiment of the glass green sheet of the present invention. [Figure 3] It is a cross-sectional view schematically showing an SOFC system according to one embodiment of the glass green sheet of the present invention. [Mode for Carrying Out the Invention]
[0019] Hereinafter, one example of the glass green sheet of the present invention will be described in detail with reference to the drawings. [Examples]
[0020] FIG. 1 is a process chart illustrating an example of the manufacturing process of the glass green sheet 10 which is an example of the present invention. First, in the mixing step P1, a plasticizer, a release agent, an antifoaming agent, and an aqueous solvent are added to and mixed with glass powder and an acrylic binder, which are raw materials of the glass green sheet 10.
[0021] Among these, the glass powder is the main component of the green sheet 10, and is fused and solidified by firing treatment. As such glass powder, conventionally known ones can be used without particular limitation within the range where the effects of the present invention are exhibited. For example, borosilicate glass is used in the present example. This borosilicate glass contains 30 to 75 mol% of MgO+CaO+BaO (30 mol% or more and 75 mol% or less; the same applies hereinafter), 1 to 10 mol% of ZnO, 15 to 45 mol% of B₂O₃, 15 to 35 mol% of Al₂O₃+SiO₂, 0 to 1 mol% of Cu₂O, 0 to 1 mol% of Fe₂O₃, and 0 to 1 mol% of NiO, respectively.
[0022] The particle size of the glass powder is not particularly limited, but is typically on the micron scale. In the present example, glass powder having a particle size distribution with a D50 particle size of 10 μm or more and 30 μm or less is particularly used. In this way, by using a glass powder in which glass particles with a large particle size and glass particles with a small particle size are mixed, the gaps generated between the glass particles can be reduced, so that when the glass sheet is used for sealing, a dense gas sealing portion can be easily formed. The "D50 particle size" in the present specification refers to the particle size corresponding to 50% cumulative from the fine particle side in the volume-based particle size distribution measured by the laser diffraction / light scattering method.
[0023] The binder is a component that binds each component in the green sheet to enhance the shape integrity of the sheet. In the sealing green sheet of the present example, since an aqueous solvent is used, an aqueous binder that is suitably dispersed in the aqueous solvent is used. Specifically, a water-soluble acrylic resin having carboxyl groups in side chains and terminals is used as the aqueous binder. Here, the carboxyl group is a hydrophilic group. In addition, since the carboxyl groups are provided on the side chains and terminals of the resin material, the dispersibility in the aqueous solvent is favorable.
[0024] Suitable examples of resin materials used in the above-mentioned aqueous binder include acrylic resins and polyether resins having carboxyl groups in at least one of the side chains and terminals. These resin materials can be uniformly dispersed in an aqueous solvent to impart suitable shape integrity to the green sheet, and can also be suitably removed by low-temperature degreasing treatment. From the viewpoint of more suitably preventing firing defects due to residual aqueous binder, the weight loss rate of the resin material used as the aqueous binder after heat treatment at 400°C is preferably 80% or more, more preferably 85% or more, even more preferably 90% or more, and particularly preferably 95% or more. Furthermore, there is no particular upper limit to the weight loss rate after such heat treatment, and it may be 100% or less, or 99% or less.
[0025] Plasticizers are components that impart strength, flexibility, and moisture retention to the green sheet, thereby improving its moldability and storability. In this embodiment, the plasticizer contains at least one of a trivalent or higher alcohol and a polyether. These resin materials can impart suitable strength and flexibility to the green sheet even when dispersed in an aqueous solvent, thus effectively preventing molding defects and damage during sheet molding. Suitable examples of trivalent or higher alcohols include polyglycerins such as diglycerin, triglycerin, and tetraglycerin, as well as glycerin, trimethylolmethane, trimethylolpropane, pentaerythritol, albitol, sorbitol, xylose, arabinose, glucose, galactose, sorbose, fructose, palatinose, maltotriose, and maleitose. Suitable examples of polyethers include polyoxyethylene polyglyceryl ether and polyoxypropylene polyglyceryl ether. Among these, glycerin and polyoxyethylene polyglyceryl ether are particularly preferable because they can impart suitable strength and flexibility, as well as suitable moisture retention, and are therefore also preferable from the viewpoint of storage of the molded green sheet.
[0026] Furthermore, in the sealing green sheet disclosed herein, a resin material with an average molecular weight of 1500 or less is used as the plasticizer. If the average molecular weight of the plasticizer is too high, the plasticizer with long molecular chains tends to bind excessively with the glass powder, causing the green sheet precursor (e.g., granulated powder) to become rubbery, making sheet molding difficult. In this specification, "average molecular weight" refers to the weight-average molecular weight.
[0027] Furthermore, a fatty acid emulsion was used as a mold release agent. In addition, a straight-chain saturated hydrocarbon with 5 to 20 carbon atoms was used as an antifoaming agent.
[0028] These binders, plasticizers, release agents, and defoamers are all organic materials containing organic components. In this example, the amount of these organic materials added is prepared to be 9 to 14 wt% of the total glass green sheet. Specifically, the binder is added at a rate of 7.6 to 11.8 wt% of the total glass green sheet, the release agent at a rate of 0.3 to 0.4 wt%, the plasticizer at a rate of 0.9 to 1.4 wt%, and the defoamer at a rate of 0.2 to 0.3 wt%.
[0029] Returning to Figure 1, in mixing step P1, glass powder and organic material are added to prepare a slurry. Various conventionally known mixing devices such as ball mills, mixers, dispersers, and kneaders are used to mix these materials.
[0030] In the granulation powder production step P2, granulation powder, which will serve as a precursor for the glass green sheet, is produced from the mixture and solvent prepared in the mixing step P1. Specifically, for example, granulation powder can be obtained by spray-drying (aerosol granulation), where a liquid material consisting of a mixture mixed with a solvent is sprayed into a dry atmosphere and dried. By using this aerosol granulation method, particles are formed according to the size of the sprayed droplets, making it easy to adjust the size and mass of the particles in the granulation powder to the desired level in subsequent steps.
[0031] The solvent used was ion-exchanged water, that is, water from which impurities had been removed by passing it through an ion-exchange resin, which is a filter material.
[0032] In the pressure molding process P3, the granulated powder obtained in the granulated powder generation process P2 is pressure-molded, for example, by a roll molding method, to produce a sealing green sheet. In the roll molding method, a molding apparatus having a pair of rolling rolls arranged with a desired width, such as 1 mm, is used, and the granulated powder is supplied between the pair of rolling rolls. The granulated powder is then compressed and formed into a sheet by rotating each rolling roll. With this roll molding method, a sheet can be directly formed from powdered or crumbly raw material powder, eliminating the need to prepare a raw material slurry and contributing to improved work efficiency. It also contributes to the stable molding of a sealing green sheet with excellent homogeneity.
[0033] Furthermore, in the pressure molding process P3, after being formed into a sheet by the molding apparatus described above, it is punched out using a die corresponding to a predetermined shape. This yields multiple glass green sheets of the predetermined shape.
[0034] In the subsequent storage process P4, the glass green sheets, which have been given the predetermined shape in the pressure molding process P3, are stacked in the thickness direction of each sheet, i.e., laminated and stored. Since each glass green sheet has the predetermined surface shape and is in the form of a thin plate, stacking them in the thickness direction in an aligned manner improves their storage properties.
[0035] By the way, when glass green sheets are stored in a stacked manner, if the number of stacked sheets increases, the glass green sheets located at the bottom of the stack will bear a load equal to the weight of the glass green sheets stacked on top of them. When the stacked glass green sheets are used, they are peeled off one by one, but in conventional glass green sheets, this sometimes caused them to stick together. Such sticking can cause the glass green sheets to tear when peeled off, resulting in a decrease in yield.
[0036] However, it was confirmed that the glass green sheet of the present invention suppresses adhesion between sheets. The results of the verification experiments conducted by the inventors are shown below.
[0037] Figure 2 illustrates the outline of this verification experiment. As shown in Figure 2, five glass green sheets of a predetermined shape obtained by the method described above were stacked, and a weight equivalent to that of 95 glass green sheets was placed on top of them. As a result, the five glass green sheets were subjected to a load equivalent to that of 100 glass green sheets stacked together, which is an example of a storage condition.
[0038] At each of the following points, after 1 to 4 days had elapsed under these conditions, we investigated whether or not the five glass green sheets had adhered to each other. We also evaluated the moldability and flexibility of the glass green sheets. These verification experiments were carried out for three types of glass green sheets corresponding to the examples of this application (Examples 1 to 3) and three types of glass green sheets that do not correspond to the examples (Comparative Examples 1 to 3).
[0039] Table 1 is a table that explains the evaluation of several different types of glass green sheets, including their organic content, adhesion, moldability, and flexibility over time after lamination and storage.
[0040] Of these, the glass green sheets shown in Examples 1 to 3 satisfy the range of organic content in the present invention, while Comparative Example 1 falls below the lower limit of the range, and Comparative Examples 2 and 3 exceed the upper limit of the range. Regarding adhesion, ○ indicates no adhesion, △ indicates some adhesion but the green sheet can be peeled off without problems, and × indicates adhesion. Regarding the moldability of the sheet, ○ indicates that roll molding was possible in the aforementioned pressure molding process P3, and × indicates that it was not possible. Roll molding is impossible if cracks of a predetermined size or larger occur in the molded sheet. Regarding the flexibility of the sheet, ○ indicates flexibility, △ indicates some flexibility, and × indicates poor flexibility. Note that flexibility was not evaluated for those with a moldability of ×. The organic content refers to the weight ratio of organic materials, including binder, release agent, plasticizer, and defoamer, to the total weight of the glass green sheet.
[0041] [Table 1]
[0042] Thus, in Examples 1 to 3, which satisfy the range of organic content in the present invention, regardless of the number of days of storage elapsed (1 to 4 days), when peeling and removing a single sheet from the laminated green sheets, the sheet did not tear or stick together. Furthermore, the moldability was good, and the flexibility was also generally good. On the other hand, in Comparative Example 1, which was below the lower limit of organic content, as indicated by the "x" in the moldability row, it was difficult to form a sheet, and therefore, adhesion could not be evaluated.
[0043] Next, a solid oxide fuel cell (SOFC) system fabricated using the glass green sheet of this embodiment will be described. Figure 3 is a schematic cross-sectional view of the solid oxide fuel cell system.
[0044] The SOFC system 100 shown in Figure 3 comprises a single cell 110 of an anode-supported cylindrical SOFC. In this single cell 110, a dense, layered solid electrolyte 114 made of oxide ion conductors and a porous air electrode (cathode) 116 are sequentially formed on the outer surface of a cylindrical fuel electrode (anode) 112 having a porous structure. In this SOFC system 100, fuel gas (typically hydrogen (H2) gas) is supplied to the internal space 111 of the cylindrical fuel electrode 112, and oxygen (O2)-containing gas (typically air) is supplied to the air electrode 16 exposed to the outside of the single cell 110.
[0045] Examples of fuel electrodes 112 include those made of nickel (Ni) and YSZ cermet. Examples of solid electrolytes 114 include those made of yttria-stabilized zirconia (YSZ), gadolina-doped ceria (GDC), and lanthanum gallate (LaGaO3). Examples of air electrodes 116 include those made of lanthanum manganate (LaMnO3) systems such as (LaSr)MnO3 and (LaCa)MnO3, lanthanum cobaltonate systems such as LaCoO3, (LaSr)CoO3, and (LaSr)(CoFe)O3, and lanthanum titanate systems such as (LaSr)(TiFe)O3, which are perovskite-type oxides.
[0046] The SOFC system 100 includes a pair of gas pipes 120 having approximately the same diameter as the fuel electrode 12. One end face 13 of the fuel electrode 112 is in surface contact with the end face 121 of one gas pipe 120, and the other end face 115 of the fuel electrode 112 is in surface contact with the end face 23 of the other gas pipe 120. A gas sealing portion 101 is formed to cover the respective boundaries between the fuel electrode 112 and the gas pipes 120, and the fuel electrode 112 and the gas pipes 120 are sealed and joined by this gas sealing portion 101. In this SOFC system 100, the sealing green sheet with the above configuration is used to form the gas sealing portion 1.
[0047] More specifically, after attaching the glass green sheet 10 of this embodiment to the sealing area, it is fired at a temperature higher than the glass softening point to fuse and solidify, thereby forming the gas sealing portion 1. Organic matter in the glass green sheet is removed during this firing process.
[0048] The glass green sheet of this embodiment contains (a) glass powder, an aqueous solvent, and an organic component, (b) the organic component includes an acrylic binder, a plasticizer, a mold release agent, and an antifoaming agent, and (c) the organic component is 9 wt% to 14 wt% by weight relative to the entire glass green sheet, so that when the green sheets are stored in a laminated state, sticking between them can be reduced.
[0049] Furthermore, in the glass green sheet of this embodiment, since the glass powder has a D50 particle size of 10 μm or more and 30 μm or less, it is possible to reduce the adhesion between the green sheets when they are more preferably stacked and stored.
[0050] Furthermore, since the glass green sheets of this embodiment are used to form the gas sealing portion of a solid oxide fuel cell, when they are stored in stacks, the adhesion between the green sheets is reduced, allowing each sheet to be supplied appropriately when forming the gas sealing portion, and enabling the sealing portion to be formed appropriately.
[0051] Furthermore, according to the glass green sheet of this embodiment, since the glass powder is borosilicate glass, the fired glass will have excellent heat resistance and hardness.
[0052] Although the present invention has been described in detail above with reference to tables and drawings, the present invention can be implemented in other embodiments, and various modifications can be made without departing from its spirit.
[0053] For example, in the above-described embodiment, ion-exchanged water was used as the solvent, but it is not limited to this. For example, distilled water or the like can be used.
[0054] Furthermore, while the above-described examples show an example of the composition of the borosilicate glass material, the composition is not limited to this. The composition can be changed as needed to adjust the melting point according to the application of the glass green sheet.
[0055] Furthermore, in the above-described embodiment, the glass green sheet was punched out in a rectangular shape as shown in Figure 1, but the embodiment is not limited to this. It can be any shape.
[0056] It should be noted that the above is merely one embodiment, and although other examples are not provided, the present invention can be implemented in various modified and improved forms based on the knowledge of those skilled in the art, without departing from its spirit. [Explanation of Symbols]
[0057] 10 Glass Green Sheets 100 SOFC System 101 Gas sealing section 110 single cells 112 Fuel electrode (anode) 113, 115 Ends of fuel electrodes 114 Solid electrolyte layer 116 Air electrode (cathode) 120 gas pipe
Claims
1. A glass green sheet containing glass powder, an aqueous solvent, and an organic component, The aforementioned organic component includes an acrylic binder, a plasticizer, a mold release agent, and an antifoaming agent. The organic component is present in an amount of 9 wt% to 14 wt% relative to the entire glass green sheet. A glass green sheet characterized by its features.
2. The glass powder has a D50 particle size of 10 μm or more and 30 μm or less. The glass green sheet according to feature 1.
3. Used in forming the gas sealing portion of solid oxide fuel cells, Glass green sheet according to feature 1 or 2
4. The aforementioned glass powder is borosilicate glass. Glass green sheet according to feature 1 or 2
Citation Information
Patent Citations
Green sheet for sealing
JP2020167093A